WATERFALL ANALYSIS APPROACH IN THE DEVELOPMENT OF THE BONEN CAVE TOURISM WEBSITE AS A DIGITAL INFORMATION AND PROMOTION MEDIA - Robertho Kadji; Irene Augusta Boymau; Lidia Paskalia Nipu; Ika Fitri Krisnasiwi (RADJA PUBLIKA, 2025)
This research covers the developing of the Bonen Cave tourism website as a digital platform for promoting geotourism, employing the Waterfall model of software development. The project aims to design and implement a website that effectively conveys the distinctive values of Bonen Cave in Baumata Village, Kupang, acknowledging the increasing significance of digital media in promoting tourism visibility, especially for geotourism sites with substantial geological and cultural heritage. The method consists of five successive phases: requirements analysis, system design, implementation, testing, and deployment. The data collection process encompassed stakeholder interviews and field surveys to ensure website features corresponded with local requirements and visitor anticipations. An accessible and responsive design was developed using a no-code website builder. The finished project, geowisatakupang.fun, encompasses multimedia information, interactive services, and functionalities designed to facilitate education, preservation, and community involvement. Testing validated the site's usability and operation across various devices. The project illustrates how organized digital development may enhance local communities, facilitate conservation initiatives, and advance sustainable tourism via accessible online platforms. Ongoing assessment and prospective incorporation of augmented reality and mobile applications are advised to improve user experience and sustain long-term effects.